Targeting the IRE1α/XBP1 and ATF6 Arms of the Unfolded Protein Response Enhances VEGF Blockade to Prevent Retinal and Choroidal Neovascularization - Liu, Li (American Society for Investigative Pathology, 2013)
Although anti-vascular endothelial growth factor (VEGF) treatments reduce pathological neovascularization in the eye and in tumors, the regression is often not sustainable or is incomplete. We investigated whether vascular endothelial cells circumvent anti-VEGF therapies by activating the unfolded protein response (UPR) to override the classic extracellular VEGF pathway. Exposure of endothelial cells to VEGF, high glucose, or H(2)O(2) up-regulated the X-box binding protein-1/inositol-requiring protein-1 (IRE1) α and activating transcription factor 6 (ATF6) arms of the UPR compared with untreated cells. This was associated with increased expression in α-basic crystallin (CRYAB), which has previously bound VEGF. siRNA knockdown or pharmacological blockade of IRE1α, ATF6, or CRYAB increased intracellular VEGF degradation and decreased full-length intracellular VEGF. Inhibition of IRE1α, ATF6, or CRYAB resulted in an approximately 40% reduction of in vitro angiogenesis, which was further reduced in combination with a neutralizing antibody against extracellular VEGF. Blockade of IRE1α or ATF6 in the oxygen-induced retinopathy or choroidal neovascularization mouse models caused an approximately 35% reduction in angiogenesis. However, combination therapy of VEGF neutralizing antibody with UPR inhibitors or siRNAs reduced retinal/choroidal neovascularization by a further 25% to 40%, and this inhibition was significantly greater than either treatment alone. In conclusion, activation of the UPR sustains angiogenesis by preventing degradation of intracellular VEGF. The IRE1α/ATF6 arms of the UPR offer a potential therapeutic target in the treatment of pathological angiogenesis.